Problem-Based Learning with Deep Learning for Mathematical Reasoning in Vocational High School Students - Proborini, Ellen; Asy'ari, Fajar Husain (Universitas Sarjanawiyata Tamansiswa, 2026)
Mathematical reasoning ability is an important skill that students need to have in order to analyze, compile evidence, and solve mathematical problems. The observation results show that the mathematical reasoning ability of grade XII students of SMK Wongsorejo Gombong is still relatively low. This could be caused by the application of passive learning models and less stimulation of higher-order thinking. The Problem-based Learning model is known as one of the effective learning models in maximizing reasoning and problem-solving skills. This study aims to determine whether there is a difference between the problem-based learning model with the Deep Learning, problem-based learning, and Direct learning approaches on students' mathematical reasoning abilities in mathematics lessons on geometric transformations. This study used 3 samples taken by random sampling method. The conclusion shows that the problem-based learning with Deep learning model provides better results than the problem-based learning and direct learning models, while the problem-based learning model provides better results than direct learning on students' mathematical reasoning abilities.